2009
DOI: 10.1038/hdy.2009.132
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic characterization of a temperature-sensitive conditional lethal in Drosophila melanogaster

Abstract: Genetic variation that is expressed only under specific environmental conditions can contribute to additional adverse effects of inbreeding if environmental conditions change. We present a proteomic characterization of a conditional lethal found in an inbred line of Drosophila melanogaster. The lethal effect is apparent as a large increase in early mortality at the restrictive temperature (29 1C) as opposed to normal survival at the permissive temperature (20 1C). The increased mortality in response to the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
0
18
1
Order By: Relevance
“…Since then, technologies have been developing fast and state of the art methods now enable identification and quantification of sometimes thousands of proteins in organisms such as Escherichia coli (Soufi et al, 2015). In spite of this, studies on thermal acclimation responses in arthropods have rarely identified more than a few hundred proteins (Colinet et al, 2007(Colinet et al, , 2013Pedersen et al, 2010;Wei et al, 2015), making investigation of complex physiological changes in response to thermal acclimation difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, technologies have been developing fast and state of the art methods now enable identification and quantification of sometimes thousands of proteins in organisms such as Escherichia coli (Soufi et al, 2015). In spite of this, studies on thermal acclimation responses in arthropods have rarely identified more than a few hundred proteins (Colinet et al, 2007(Colinet et al, , 2013Pedersen et al, 2010;Wei et al, 2015), making investigation of complex physiological changes in response to thermal acclimation difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Pedersen et al [13] performed a proteomic analysis of an inbred strain of D. melanogaster that suffered from extreme heat-sensitivity. They identified 45 proteins that were differentially regulated in response to the restrictive conditions, with an overrepresentation of proteins associated with oxidative phosphorylation and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…This is a great omission, as functional genomic studies of inbreeding are invaluable for dissecting many yet unsolved problems within evolutionary biology, conservation biology, agriculture, and medical sciences [7][9]. Proteome analysis is suitable as an approach to link genotypic with phenotypic effects at the organismal level, and some studies have been successful in identifying and characterizing genotypic differences using proteomic methods [10][13]. With the increasing use of genome-wide technologies, data are emerging that showcase the complexity of the whole organism responses [13][16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations